Thin Film Nanocomposite Membrane Filled with Metal-Organic Frameworks UiO-66 and MIL-125 Nanoparticles for Water Desalination - Kadhom, Mohammed; Hu, Weiming; Deng, Baolin (Membranes (Basel), 2017)
Knowing that the world is facing a shortage of fresh water, desalination, in its different forms including reverse osmosis, represents a practical approach to produce potable water from a saline source. In this report, two kinds of Metal-Organic Frameworks (MOFs) nanoparticles (NPs), UiO-66 (~100 nm) and MIL-125 (~100 nm), were embedded separately into thin-film composite membranes in different weight ratios, 0%, 0.05%, 0.1%, 0.15%, 0.2%, and 0.3%. The membranes were synthesized by the interfacial polymerization (IP) of m-phenylenediamine (MPD) in aqueous solution and trimesoyl chloride (TMC) in an organic phase. The as-prepared membranes were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), contact angle measurement, attenuated total reflection Fourier transform infrared (ATR FT-IR) spectroscopy, and salt rejection and water flux assessments. Results showed that both UiO-66 and MIL-125 could improve the membranes’ performance and the impacts depended on the NPs loading. At the optimum NPs loadings, 0.15% for UiO-66 and 0.3% for MIL-125, the water flux increased from 62.5 L/m2 h to 74.9 and 85.0 L/m2 h, respectively. NaCl rejection was not significantly affected (UiO-66) or slightly improved (MIL-125) by embedding these NPs, always at >98.5% as tested at 2000 ppm salt concentration and 300 psi transmembrane pressure. The results from this study demonstrate that it is promising to apply MOFs NPs to enhance the TFC membrane performance for desalination.